Impressions of Guangzhou city in Qing dynasty export paintings in the context of trade economy: a color analysis of paintings based on k-means clustering algorithm - Jinghui Ao; Ziying Ye; Weicong Li; Shanshan Ji (Heritage Science, 2024)
Abstract Study on export paintings has gradually shifted from artistic form to cultural connotation, with an emphasis on cross-cultural communication. Although the economic and social dimensions of their artistic value have been explored, few studies delve into the connection between Qing-era Guangzhou's trade culture and its color characteristics. Utilizing the HSV color model and the k-means algorithm, this study analyzes the color traits of 35 export paintings depicting Guangzhou landscapes and works from the "Thirteen-houses commercial zone," revealing Qing-era Guangzhou's urban impressions and Sino-Western artistic interactions. Key findings include: (1) the hue pixel range in Guangzhou export paintings primarily spans 10°–60° and 120°–250° (dominated by red and yellow-green), saturation values range from 1–82% (primarily low saturation), and value values range from 11–94% (with a wide variance); (2) compared to traditional Chinese paintings, the transformation from pure color (正色) → inter-color (间色) → projection-perspective and light source illustrates both the blending of Eastern and Western artistic cultures and a diminishing influence of traditional ceremonial culture; (3) in contrast with Western artworks, some Guangzhou export paintings display a Westernization trend in color structures, evident in vibrant colors and stark chiaroscuro contrasts. As bespoke art commodities, export paintings microscopically reflect Guangzhou's unique trade culture and socio-political dynamics. The shifts in color schemes, integration of realistic styles, and human-centric characteristics unveil the intricate interplay between quasi-realism and transcendental aesthetics in Qing-era Guangzhou, as well as the nuanced dynamics between social capital and art within a global trade network.